Phytochemical diversity and anticancer potential of Etlingera elatior fruits across ecological regions in Aceh, Indonesia - NUZUL ASMILIA; WIDYA SARI; RISA NURSANTY; SAUDAH SAUDAH; ZUMAIDAR ZUMAIDAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Asmilia N, Sari W, Nursanty R, Saudah, Zumaidar. 2025. Phytochemical diversity and anticancer potential of Etlingera elatior fruits across ecological regions in Aceh, Indonesia. Biodiversitas 26: 5423-5429. Etlingera elatior (Zingiberaceae) fruit is a traditional Acehnese medicinal plant known for its diverse bioactive compounds. This study investigated the phytochemical diversity, antioxidant properties, cytotoxicity, and anticancer potential of E. elatior fruits collected from three regions of Aceh: Pidie, the Gayo Highlands, and Simeulue Island. Qualitative and quantitative screenings were performed to assess secondary metabolites, Total Phenolic Content (TPC), and Total Flavonoid Content (TFC). Antioxidant capacity was performed by the DPPH assay, cytotoxicity by the Brine Shrimp Lethality Test (BSLT), and anticancer activity by the MTT assay against MCF-7 breast cancer cells. The results revealed clear regional differences in phytochemical profiles and bioactivities. Simeulue fruits exhibited the highest TPC and TFC, while extracts from the Gayo Highlands showed the strongest antioxidant and cytotoxic activities. Notably, the Gayo extracts also demonstrated the most potent anticancer activity, significantly inhibiting MCF-7 cell proliferation. These findings highlight the ecological influence on phytochemical diversity and biological activity of E. elatior, with altitude and geographic conditions shaping metabolite accumulation. Overall, the study demonstrates that E. elatior fruits, particularly those from the Gayo Highlands, possess considerable anticancer potential. This underscores the importance of conserving local biodiversity and supports the development of E. elatior as a natural source for novel anticancer agents. Further research should prioritize isolation of active constituents, molecular pathway analysis, and in vivo validation to advance its development for nutraceutical and phytopharmaceutical applications.